2021
DOI: 10.1186/s13046-021-01997-5
|View full text |Cite
|
Sign up to set email alerts
|

An immunotherapeutic approach to decipher the role of long non-coding RNAs in cancer progression, resistance and epigenetic regulation of immune cells

Abstract: Immunotherapeutic treatments are gaining attention due to their effective anti-tumor response. Particularly, the revolution of immune checkpoint inhibitors (ICIs) produces promising outcomes for various cancer types. However, the usage of immunotherapy is limited due to its low response rate, suggesting that tumor cells escape the immune surveillance. Rapid advances in transcriptomic profiling have led to recognize immune-related long non-coding RNAs (LncRNAs), as regulators of immune cell-specific gene expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 166 publications
(123 reference statements)
0
5
0
Order By: Relevance
“…Upregulation of its expression can increase anti-tumor response. It is indicated that GAS5 has a role in increased NK cell cytotoxicity and that it is also involved in initiation and phagophore nucleation [ 40 ]. All of this shows that GAS5 could potentially be an important therapeutic target in AML as well.…”
Section: Discussionmentioning
confidence: 99%
“…Upregulation of its expression can increase anti-tumor response. It is indicated that GAS5 has a role in increased NK cell cytotoxicity and that it is also involved in initiation and phagophore nucleation [ 40 ]. All of this shows that GAS5 could potentially be an important therapeutic target in AML as well.…”
Section: Discussionmentioning
confidence: 99%
“…Of these 13, 6 genes (RNF10, IFFO2, SLC17A5, UBXN2B, ZNF117, and ZNF488) have previous links to neurodegenerative diseases, while IFFO2 participates in muscle control [43][44][45][46][47][48] and 5 other genes (CECR7, STMP1, TRAF31P2-AS1, and LOC401127) [49][50][51][52] have roles in in ammation, bone, and autoimmune diseases. The remaining two genes -CEP78 and NUDT18 -encode for a centrosomal protein and a hydrolase of the Nudix superfamily, respectively.…”
Section: Meta-analysis Of Dge In Neurologic Tissuementioning
confidence: 99%
“…In nervous tissue, our meta-analysis detected 13 significant genes in the SDID comparison (Table 6). Of these 13, 6 genes (RNF10, IFFO2, SLC17A5, UBXN2B, ZNF117, and ZNF488) have previous links to neurodegenerative diseases, while IFFO2 participates in muscle control [43][44][45][46][47][48] and 5 other genes (CECR7, STMP1, TRAF31P2-AS1, and LOC401127) [49][50][51][52] possess links to inflammation, bone, and autoimmune diseases. The remaining two genes -CEP78 and NUDT18 -encode for a centrosomal protein and a hydrolase of the Nudix superfamily, respectively.…”
Section: Meta-analysis Of Dge In Nervous Tissuementioning
confidence: 99%